Research handbook on global governance, business and human rights - Marx, Axel; Calster, Geert van; Wouters, Jan; Otteburn, Kari; Otteburn, Kari; Lica, Diana; Lica, Diana (Research handbooks on globalisation and the law series, 2022)
"This essential Research Handbook provides a comprehensive and critical assessment of the global governance instruments related to business and human rights from an interdisciplinary perspective. Contributions from a diverse range of leading international scholars offer an overview of the existing literature and rapidly-evolving research discipline, as well as identifying key trends and outlining an ambitious future research agenda. The Research Handbook first examines governance initiatives that operate across economic sectors, discussing both public and private initiatives at state, regional and international levels that seek to develop, implement and enforce rules with regard to the impacts of transnational business activities on human rights. Chapters then investigate particular economic sectors - including textiles, electronics, agro-chemical, construction, and finance - to assess the ways in which different initiatives attempt to mitigate risks and address business-related human rights abuses within each sector. Scholars of law, regulatory governance, global governance, management, human rights and social sciences who are interested in gaining a deeper understanding of the emerging business and human rights regime will find this Research Handbook a crucial read. It will also prove a useful and thorough introduction for students, scholars and practitioners new to the field of business and human rights"--